The threshold of the monstrous, between dehumanization and necro-capitalism (Itinera, 2023)
The subject of the following contribution is a discussion of the theses in R.L.Smith's volume 'Making Monster,' on the relationship between processes of dehumanization and the production of monstrosity. Reading the multiple facets of this link, the contribution tries to highlight some lines of analysis. The first of analysis concerns on the epistemic status of the concept of dehumanization. The second, on the other hand, concerns the actual dimensions of the processes of monstrosity production within the multiple social, temporal and political layers of the concept of crisis.
Keywords: analogy; imagination; metaphor; method of abstraction